Timing of Nitrogen Fertilisation and the Effect of Poultry Manure on the Performance of Grapevines on Sandy Soil. I. Soil Analysis, Grape Yield and Vegetative Growth - Conradie, W.J. (South African Journal of Enology and Viticulture, 2017)
A field trial with two Vitis vinifera L. cultivars, viz. Bukettraube (white) and Heroldrebe (red), grafted onto Ramsey, was carried out over a nine-year period on a sandy, duplex soil. The control (No) received no N, while three other treatments each received 50 kg N/ha in inorganic form. The N was applied either as three equal installments, split between budbreak, fruitset and post-harvest (N1), or as a single application at budbreak (N2), or as a single postharvest application (N3). A fifth treatment (N4) received 50 kg N/ha at budbreak in the form of poultry manure. A winter cover crop (rye) was sown after harvest, chemically controlled before budbreak with a herbicide and left as an organic mulch on the soil surface. This cover crop management system maintained the soil’s organic material (SOM) at the original level for all inorganic treatments, while N4 increased SOM. On average, Bukettraube yielded 11.4 t/ha, in comparison to only 6.0 t/ha for Heroldrebe. Yields of the four fertilised treatments (Ni, N2, N3 and N4) were comparable for each individual cultivar. Relative to N0, fertilisation increased yields by 24% and 48% for Bukettraube and Heroldrebe, respectively. In comparison to the control, all four fertilisation treatments increased shoot mass, with Nz being significantly higher than Ni, NJ and N4. The fact that Nz stimulated shoot growth, without a concomitant increase in yield, indicated that a single application of N at bud break can cause excessive growth, even on low-potential soil. In the case of Bukettraube, grapes from the Nz treatment showed the highest incidence of bunch rot during some seasons. Under the cultivation practices followed in this trial, split applications of N (budbreak, fruitset, post-harvest) or a single application during the post-harvest period was compatible with the most desirable pattern of vine growth and fruit development. Application of poultry manure was not associated with any specific advantages or disadvantages. Soil analysis showed that the control vines were fairly well supplied with mineral N at budbreak, but under-supplied at the time of fruitset.